HUBUNGAN DUKUNGAN SOSIAL DAN NON SOSIAL DENGAN MOTIVASI BELAJAR PADA PESERTA UKMPPD - Intan Putri Permata Hati; Hetti Rusmini; Vira Sandayanti (Program Studi Psikologi Universitas Malahayati, 2021)
ABSTRACT: RELATIONSHIP BETWEEN SOCIAL AND NON-SOCIAL SUPPORT WITH LEARNING MOTIVATION IN PARTICIPANTS OF UKMPPDStudents who have completed the Physician Professional Education stage are required to take the Medical Doctor Profession Program Student Competency Test (UKMPPD). This study aims to determine the relationship between social and non-social support and learning motivation among UKMPPD’s participant students. This research is an analytical study with a cross sectional design. The research sample consisted of 170 UKMPPD participants for the November 2019 period at Malahayati University. Data collected using a social support scale, non-social support scale & learning motivation scale. Data were analyzed using Spearman's Rank. The results showed that there was a significant relationship between social and non-social support and learning motivation among UKMPPD participants for the November 2019 period at Malahayati University. Keywords: learning motivation, social support, non social support, UKMPPD Mahasiswa yang telah menyelesaikan tahap Pendidikan Profesi Dokter wajib mengikuti Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD). Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan sosial dan non sosial dengan motivasi belajar pada mahasiswa peserta UKMPPD. Penelitian ini merupakan penelitian analitik dengan desain cross sectional. Sampel penelitian berjumlah 170 peserta UKMPPD periode November Tahun 2019 di Universitas Malahayati. Pengambilan data menggunakan skala dukungan sosial, skala dukungan non sosial & skala motivasi belajar. Data dianalisis menggunakan Rank Spearman’s. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara dukungan sosial dan non sosial dengan motivasi belajar pada mahasiswa peserta UKMPPD periode November tahun 2019 di Universitas Malahayati. Kata Kunci: motivasi belajar, dukungan sosial, dukungan non sosial, UKMPPD